Investigating the impact of long-term bristlegrass coverage on rhizosphere microbiota, soil metabolites, and carbon–nitrogen dynamics for pear agronomic traits in orchards - Shi, Chunhui; Wang, Xiaoqing; Jiang, Shuang; Xu, Jianfeng; Luo, Jun (Frontiers in Microbiology, 2024)
Background Grass coverage (GC) under no-tillage systems in orchards signifcantly infuences underground carbon (C) and nitrogen (N) sequestration, primarily through promoting mineral nutrient utilization by rhizospheric microorganisms. However, the comprehensive impact of GC on microbial communities and plant responses using soil metabolomics remains inadequately recognized. Methods We investigated two rhizosphere types established since 2002: bristlegrass (Setaria viridis (L.) P. Beauv.) coverage (SC) and clean cultivation (CC) to assess their efects on soil parameters, enzyme activities, and key pear agronomic traits, including yield (single fruit weight (SFW)) and qualities (soluble solids content (SSC), and total soluble sugar (TSS)). We combined microbiological analysis (16S rRNA sequencing) and non-targeted metabolomics (UPLC-MS/MS and GC–MS) to explore how microbial communities infuence fruit agronomic traits and soil nutrient dynamics in pear orchards under SC conditions. Results Our fndings indicate that SC signifcantly enhances soil organic carbon (SOC), soil organic nitrogen (SON), the C:N ratio, and available nitrogen (AN). Moreover, SC leads to pronounced increases in soil enzyme activities involved in the C cycle and storage, including soil sucrase, β-glucosidase, polyphenol oxidase and cellulase. Microbiome analysis revealed substantial diferences in microbial community composition and diversity indices between SC and CC rhizosphere soils within the 0–40 cm depth. Metabolomic analysis demonstrated significant alterations in metabolite profiles across both the 0-20 cm and 20-40 cm layers under SC conditions. The identifed metabolites primarily involve sugar and amino acid-related metabolic pathways, refecting perturbations in C and N metabolism consistent with shifts in bacterial community structure. Several plant growth-promoting rhizobacteria (PGPRs) taxa (e.g., Haliangium, Bacteroides, mle1-7, Subgroup_22, Ellin6067, MND1, Flavobacterium, and Cellvibrio) were enriched under SC, associated with metabolites such as sucrose, N-acetyl-D-glucosamine, N-acetyl-L-glutamic acid, rhamnose, UDP-GlcNAc and D-maltose. These fndings suggest their roles in promoting C and N sequestration processes through sucrose synthesis and glycolytic pathways in the soil, which was signifcantly correlated with the formation of agronomic traits such as fruit yield, SFW SSC and TSS (p<0.05), and SC treatments signifcantly increased yields by 35.40–62.72% and sucrose content in TSS by 2.43–3.96 times than CC treatments. Conclusion This study provides valuable insights into the efects of SC on soil microbial communities and plant physiology, enhancing our understanding of their implications for sustainable orchard management.